2018
DOI: 10.1155/2018/2538765
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Motion Analysis of Tai Chi Chuan: The Upper Extremity Movement

Abstract: The quantitative and reproducible analysis of the standard body movement in Tai Chi Chuan (TCC) was performed in this study. We aimed to provide a reference of the upper extremities for standardizing TCC practice. Microsoft Kinect was used to record the motion during the practice of TCC. The preparation form and eight essential forms of TCC performed by an instructor and 101 practitioners were analyzed in this study. The instructor completed an entire TCC practice cycle and performed the cycle 12 times. An ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, the slow movements in Tai Ji are also reported to promote brain function and improve cognitive flexibility, which is more holistic and focuses on the patient's biopsychosocial model as compared to conventional therapy; therefore, Tai Ji is known as the moving meditation ( 51 , 52 ). Since Tai Ji is an art, the practitioner may also choose to perform them at a faster pace once the practitioner is familiar with the movements or during ‘Tui Shou’ (Tai Ji Sparring), which carries different benefits such as cardiovascular health ( 53 , 54 ). Besides, the fundamental stance in Tai Ji, known as horse-riding stance or horse-riding posture ‘ma bu’, requires eccentric contraction of the lower limb muscles, particularly the quadriceps, and strengthens the lower limb, which is vital in static and dynamic balance ( 55 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the slow movements in Tai Ji are also reported to promote brain function and improve cognitive flexibility, which is more holistic and focuses on the patient's biopsychosocial model as compared to conventional therapy; therefore, Tai Ji is known as the moving meditation ( 51 , 52 ). Since Tai Ji is an art, the practitioner may also choose to perform them at a faster pace once the practitioner is familiar with the movements or during ‘Tui Shou’ (Tai Ji Sparring), which carries different benefits such as cardiovascular health ( 53 , 54 ). Besides, the fundamental stance in Tai Ji, known as horse-riding stance or horse-riding posture ‘ma bu’, requires eccentric contraction of the lower limb muscles, particularly the quadriceps, and strengthens the lower limb, which is vital in static and dynamic balance ( 55 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be done at least three times a week to guarantee this effect. In [7] the Microsoft Kinect is used to record the spatial coordinates of the joints of the upper limbs of the body during the practice of Tai Chi Chuan as well as the data in order to perform a quantitative and qualitative analysis of the joint positions and the angle of the elbow joint. A study was conducted by [8] with participants from a trial on the effects of a 12-week Tai Chi training on the risk of ischemic stroke in the elderly, and this study showed that regular exercise Tai Chi can have positive benefits in terms of improving physical health and mental state of elderly.…”
Section: Introductionmentioning
confidence: 99%